2020
DOI: 10.1039/d0se00782j
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the temperature coefficients of carbon-based perovskite solar cells

Abstract: Temperature-dependent studies on carbon-based perovskite solar cells (c-PSCs) manifest a less explored area of research compared with the numerous studies on improving the power conversion efficiency (PCE) and stability of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…In the last several years, Perovskite PV showed tremendous improvements and their efficiency closely matched to inorganic type PV cells [31]. Moreover, temperature coefficient of Perovskite technology has weaker temperature impact compared to first and second generation PV systems [32]. Perovskite PVs still suffer from long term stability and use of lead has environmental concern.…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, Perovskite PV showed tremendous improvements and their efficiency closely matched to inorganic type PV cells [31]. Moreover, temperature coefficient of Perovskite technology has weaker temperature impact compared to first and second generation PV systems [32]. Perovskite PVs still suffer from long term stability and use of lead has environmental concern.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional gold, silver and aluminium electrodes are the most efficient ones in terms of PCE, although their large scale cost of production is a matter of concern along with their reactivity with perovskite materials to facilitate decomposition 38 . Standard PSC with carbon-based back contact is a suitable solution to substitute noble metals due to their low cost, high conductivity, eventual low-temperature processing and work function close to gold 39 43 . Various allotropes of carbon as well as composite HTM-based carbon have been extensively used as a counter electrode to facilitate the better performance of devices 18 , 44 – 48 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the latitude and elevation of the site, the installation angle and orientation of PV panels, shading, and temperature are reported to be important parameters. [21][22][23][24][25][26] A study in Korea found that the performance of semitransparent PV panels decreases by approximately 0.5% with each 1 C increase in the PV panel temperature. 24 Yadav and Bajpai reported similar temperature dependency of PV panel performance.…”
Section: Introductionmentioning
confidence: 99%